Effect of whey protein on thickness, water vapour transmission rate, and water content of gelatin film - Fahrullah, Fahrullah; Rahmawati, Lilik; Kartika, Kartika; Ulkiyah, Kalisom; Yulianto, Wahid (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Packaging is a tool used to protect products from physical damage; edible films can improve food quality and reduce plastic-based packaging materials. This study aimed to determine the effect of adding whey protein concentration on gelatin edible film thickness, water vapour transmission rate, and moisture content. This research used a completely randomized design with 4 treatments and 3 replications. The treatments consisted of P0 (0 g whey: 2 g gelatin), P1 (0.05 g whey: 2 g gelatin), P2 (0.10 g whey: 2 g gelatin), P3 (0.15 g whey: 2 g gelatin). The addition of whey protein had a significant effect (P<0.01) on the thickness of the gelatin film. However, no significant effect (P>0.05) was found on the water vapour transmission rate and moisture content. Nonetheless, employing whey protein can reduce the water vapour transmission rate and increase the moisture content of edible gelatin film. The findings suggest that incorporating whey protein can enhance the physicochemical properties of gelatin films. Using whey protein at a concentration of 0.05 g is deemed the optimum treatment.